Diagnosing Growth Hormone Deficiency in Adults - Nigel Glynn; Amar Agha (International Journal of Endocrinology)
Adult growth hormone (GH) deficiency is a recognised syndrome associated with adverse phenotypic, metabolic, and quality-of-life features which improve in many patients when GH is substituted. The appropriate selection of patients at risk of growth hormone deficiency (GHD) is the crucial first step in arriving at a correct diagnosis. Although multiple diagnostic modalities are available including a 24-hour serum GH profile, stimulated GH levels, and insulin-like growth factor-1 (IGF-1) levels, the use of dynamic tests for GH reserves is required in most cases. This paper discusses the utility and drawbacks of the various testing modalities with reference to international guidelines. Regardless of the test chosen, clinical pitfalls including age and obesity must be taken into account. In addition, there is considerable analytical variation in the biochemical measurements of GH and IGF-1 which must be considered before making a diagnosis of GHD in adulthood.